Prevention and management of carcinoid crises in patients with high-risk neuroendocrine tumours undergoing peptide receptor radionuclide therapy (PRRT): Literature review and case series from two Australian tertiary medical institutions. (May 2018) - Tapia Rico, Gonzalo; Li, Minmin; Pavlakis, Nick; Cehic, Gabrielle; Price, Timothy J.
Highlights: Introduction to what currently is an unrecognised clinical problem, ie induced carcinoid crisis from PRRT. Review of cases illustrating the clinical situation. Review of literature published for various protocols to prevent carcinoid crisis from the surgical and anaesthetic setting. Proposal of a protocol that could be used by NET centres treating patients who are undergoing PRRT therapy. Abstract: Peptide receptor radionuclide therapy (PRRT) is an important therapeutic option for somatostatin receptor (SSTR) positive metastatic and/or inoperable neuroendocrine tumours (NETs). However, in patients with poorly controlled carcinoid syndrome, it may lead to an acute flare of carcinoid symptoms or even carcinoid crisis. We report seven patients who received PRRT with ( 177 Lu-DOTA 0, Tyr 3 ) octreotate ( 177 Lu-octreotate-LuTate) across two Australian tertiary medical institutions who developed acute flare of carcinoid symptoms/carcinoid crisis during/after PRRT. Cases were identified as high-risk due to previous history of carcinoid crises, high tumour burden and markedly elevated tumour markers. We propose a protocol to prevent and manage severe carcinoid symptoms in high-risk patients treated with PRRT.